Dehydrated and Freeze-dried Peach Fruit: A Prolonged Shelf-life Product through Modern Drying Techniques - Fariborz Habibi; Ali Sarkhosh; Steven A. Sargent; Jeffrey K. Brecht (EDIS, 2024)
Peach (Prunus persica L. Batsch) is a valuable temperate fruit from the Rosaceae family, which also includes many other commercially important fruits such as apples and pears, apricots, cherries and plums, and blackberries, raspberries and strawberries. Peaches are known for being a rich source of bioactive compounds, including flavonoids, anthocyanins, carotenoids, phenolic compounds, and vitamins, as well as possessing a high antioxidant activity, all of which are associated with various health benefits. Furthermore, consumers greatly value high-quality peaches due to their exceptional nutritional value and enjoyable sensory attributes. This publication aims to familiarize growers, Extension agents and specialists, and the public with insight into drying methods of peach fruit, including freeze-drying and dehydration, that can extend shelf life of this commodity for year-round enjoyment.